Evaluasi Platform Elearning pada Matakuliah Metodologi Penelitian Menggunakan Model Evaluasi CIPP - Yanti, Rini Fariska; Dewi, Siska Miga (Al-DYAS, 2025)
The problem in this study is the lack of student understanding in the online learning process through the e-learning platform in the Research Methodology course and the absence of an evaluation of the effectiveness of using the e-learning platform in the learning process. The purpose of this study is to determine the evaluation of the e-learning platform in the Research Methodology course using the CIPP evaluation model which includes Context, Input, Process, and Product. Overall, the results of this study indicate that the e-learning platform has a positive impact on Research Methodology learning. Although all aspects are in the good category, the percentage value of each aspect is still close to the lower limit of the category, so there is still room for further improvement to increase the effectiveness of learning as a whole.